2000
DOI: 10.1161/01.res.87.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia in Transgenic Mice Overexpressing Human Glutathione Peroxidases

Abstract: Abstract-In response to endotoxemia induced by administration of lipopolysaccharide, a complex series of reactions occurs in mammalian tissues. During this inflammation response, cells produce different mediators, such as reactive oxygen species, a number of arachidonic acid metabolites, and cytokines. The reactive oxygen species thus generated have been suggested to produce tissue injury as a result of macromolecular damage or by interfering with regulatory processes. They may also act as important signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…A previous study showed that GPX2 is the only inducible form of GSH peroxidase in the lungs that is regulated by Nrf2 (7). A protective role of GSH peroxidase in LPS-induced inflammation has been previously reported (39). These results indicate that Nrf2-directed constitutive regulation of cellular redox status is fundamental in determining the outcome of the innate immune response.…”
Section: Figure 11supporting
confidence: 65%
“…A previous study showed that GPX2 is the only inducible form of GSH peroxidase in the lungs that is regulated by Nrf2 (7). A protective role of GSH peroxidase in LPS-induced inflammation has been previously reported (39). These results indicate that Nrf2-directed constitutive regulation of cellular redox status is fundamental in determining the outcome of the innate immune response.…”
Section: Figure 11supporting
confidence: 65%
“…Transgenic animals manifested less vascular permeability, possibly due to an increased constitutive ability of GPx1-overexpressing cells to withstand oxidative stress and toxic metabolites. A dramatic effect of GP overexpression on leukocyte behavior has been previously reported in two other inflammationrelated injury models, kidney I/R and LPS-induced septic shock (6,7). Significant resistance to injury in both models correlated with the level of key inflammatory mediators.…”
Section: Discussionsupporting
confidence: 52%
“…The generation of transgenic mice with human GPx1 genes in a C57BL/ 6 ϫ CBA/J background was previously reported (4,7). The mouse line GPE23 (containing 200 copies of the human GPx1 gene) was used for these studies.…”
Section: Transgenic Micementioning
confidence: 99%
“…Our results are also consistent with a study showing that circulatory failure induced by a large dose of lipopolysaccharides was inhibited in GSHPx TG mice. 23 The beneficial effects of GSHPx overexpression shown in the present study were not a result of its MI size-sparing effect, because the infarct size was comparable between WTϩMI and TGϩMI mice. Furthermore, its effects might not be attributable to the effects of GSHPx overexpression on hemodynamics, because blood pressure and heart rate were not altered (Table).…”
Section: Discussionmentioning
confidence: 52%